A new species of Centris (Xanthemisia) Moure, 1945 from South America with a synopsis of the known species of the subgenus in Colombia (Hymenoptera: Apidae: Centridini) - Vivallo, Felipe; Vélez, Danny; Fernández, Fernando (Zootaxa, 2013)
A synopsis of the species of Centris subgenus Xanthemisia Moure in Colombia is presented. The species identified are Centris ferruginea Lepeletier, C. lutea Friese and C. aureiventris, a new species from the Colombian Andes. Morphological characters of both sexes, distribution records and an identification key for the three species of the subgenus that occur in Colombia are provided.